Teaching About Female Genital Mutilation: Complex Question of Cultural Relativism and Preventive Movement - Nur Quma Laila; Hasse Jubba (Institut Agama Islam Negeri Kendari, 2021)
This study aims to investigate three things. First, how is the tendency of the perspective used in discussing the issue of female circumcision in society; second, what is the value base that distinguishes the practice of female circumcision in one society from another; and third, how each value base in the practice of female circumcision is realized or transformed in the feminist movement. The research was carried out with a qualitative approach where data were obtained using a literature study method by reading books, journal articles and various reports on the practice of female circumcision. The results show that studies that discuss the practice of female circumcision tend to be discussed in five perspectives, namely in the perspective of gender, culture, health, religion and law. In practice, female circumcision has a different value base from one society to another. The value bases used in female circumcision include women's initiation into adulthood; purification or cleansing, beautification; and female fertility. Different value bases become the basis for feminists to make efforts to prevent the practice of female circumcision, starting from the level of binding regulations to prevent the practice of female circumcision, community participatory dialogue to abandon the practice of female circumcision, and empowering women through education and the economy.